2020
DOI: 10.1088/1741-4326/ab680f
|View full text |Cite
|
Sign up to set email alerts
|

New rate equation model to describe the stabilization of displacement damage by hydrogen atoms during ion irradiation in tungsten

Abstract: The effect of deuterium (D) presence on the amount of displacement damage created in tungsten (W) during high-energy W-ion irradiation is investigated. For this purpose, we have performed modelling of experimental results where W was sequentially or simultaneously irradiated by 10.8 MeV W ions and exposed to 300 eV D ions. A novel displacement damage creation and stabilization model was newly developed and introduced into the MHIMS-Reservoir (Migration of Hydrogen Isotopes in MaterialS) code. It employs macros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 58 publications
9
34
0
Order By: Relevance
“…This was to the author's knowledge never experimentally observed before and means that He differently influences on HI trapping as compared to the only W irradiated and hence displacement damaged W. In the latter case it is typically observed that a diffusion front with constant D concentration is moving deeper into the sample. The simulation of the data from figure 9 showed us that we were able to get a good agreement with the experimental D depth profiles and D desorption spectrum only when the de-trapping energy in the He zone was set slightly lower (1.74 eV) as compared to the de-trapping energy for the traps due to W ion irradiation (1.82 and 2.06 eV, figure 14) which we assume are vacancy clusters and voids [63].…”
Section: Transport In He Containing W Samplesupporting
confidence: 56%
See 1 more Smart Citation
“…This was to the author's knowledge never experimentally observed before and means that He differently influences on HI trapping as compared to the only W irradiated and hence displacement damaged W. In the latter case it is typically observed that a diffusion front with constant D concentration is moving deeper into the sample. The simulation of the data from figure 9 showed us that we were able to get a good agreement with the experimental D depth profiles and D desorption spectrum only when the de-trapping energy in the He zone was set slightly lower (1.74 eV) as compared to the de-trapping energy for the traps due to W ion irradiation (1.82 and 2.06 eV, figure 14) which we assume are vacancy clusters and voids [63].…”
Section: Transport In He Containing W Samplesupporting
confidence: 56%
“…The obtained D concentrations for the plasma exposures are higher as compared to the D atom exposures. This is attributed to the lower exposure temperature (450-470 K) and higher D ion flux for the plasma experiments, where traps with lower de-trapping energy can be populated [63], which is not the case for D atom exposure at 600 K. Still we observe similar, almost linear decrease of D concentration at high annealing temperature of 1700 K, as was observed in a recent study by Zibrov et al [51]. For the 'He' side no decrease in D concentration is observed after annealing to 1700 K. We observe even an increase by 20 %, which is due to accumulation of He at high temperatures.…”
Section: Influence Of He On D Retention In Fusion Devicesmentioning
confidence: 99%
“…At an annealing temperature of 600 K about 30 % of its reference density is lost and at 800 K, approximately 50 % of the reference amount is annealed. In our previous publication [18] this defect was inferred to be single vacancies. Defect type II, that desorbs in the high-temperature D desorption peak centered at 780 K, shows no reduction in density for temperatures lower or equal to 600 K, while at 800 K around 33 % of reference defect density is annealed.…”
Section: Simulation Resultsmentioning
confidence: 84%
“…Defect type II was inferred to be small vacancy clusters in Ref. [18]. Defect type III shows no behaviour with rising annealing temperature.…”
Section: Simulation Resultsmentioning
confidence: 96%
See 1 more Smart Citation